Implications of gut microbiota dysbiosis and fecal metabolite changes in psychologically stressed mice - Zhang, Yi; Zhang, Jing; Wu, Jianmin; Zhu, Qinwen; Chen, Changrong; Li, Yanning (Frontiers in Microbiology, 2023)
Psychological stress can induce affective disorders. Gut microbiota plays a vital role in emotional function regulation; however, the association between gut microbiota and psychological stress is poorly understood. We investigated effects of psychological stress on the gut microbiome and fecal metabolites and assessed the relationship between affective disorder behavior and altered fecal microbiota. In this study, a psychological stress model was established in C57BL/6J mice using a communication box. Sucrose preference test, forced swim test, and open field test helped assess anxiety- and depression-like behaviors. Fecal microbiota transplantation (FMT) was conducted using fecal samples from stressed and non-stressed mice. Moreover, 16S rRNA gene sequencing and untargeted metabolomics were performed. After stress exposure for 14 days, a significant increase in anxiety- and depression-like behaviors was observed. FMT of “affective disorder microbiota” from psychologically stressed mice increased stress sensitivity relative to FMT of “normal microbiota” from non-stressed mice. 16S rRNA gene sequencing revealed decreased abundance of Bacteroides, Alistipes, and Lactobacillus and increased abundance of Parasutterella and Rikenellaceae_RC9_gut_group in stressed mice; furthermore, stressed mice showed differential metabolite profiles. KEGG pathway analysis indicated that differential metabolites were chiefly involved in the downregulated pathways of α-linolenic acid metabolism, taste transduction, and galactose metabolism. Alistipes and Bacteroides were mainly positively correlated and Parasutterella was mainly negatively correlated with diverse metabolites. Our findings suggest that gut microbiome dysbiosis contributes to affective disorder development in response to psychological stress.